Prepatellar Bursitis with Abscess due to Corynebacterium ulcerans. (27th July 2021) - Patil, Sachin M.; Beck, Phillip Paul; Nelson, Taylor B.; Acevedo, Andres Bran; Roland, William
Abstract : Corynebacteria are ubiquitous and reside as skin and mucosa commensals in animals. They are considered contaminants in clinical specimens, but significant clinical data points to their virulence and pathogenic potential over the last two decades. Corynebacteria can cause both community-acquired and nosocomial infections. Corynebacterium diphtheriae ( C. diphtheriae ) responsible for diphtheria has declined over the previous two decades with an increase in a similar clinical syndrome by Corynebacterium ulcerans ( C. ulcerans ) in Europe. As per recent studies, C. ulcerans shares similar virulence factors with C. diphtheriae . C. ulcerans has been implicated in airway infections, skin and soft tissue infections, lymphadenitis, wound infections, and rarely necrotizing fasciitis. Pet or farm animals have been the source of these infections to humans, as per recent reports. Strains can be either toxigenic or nontoxigenic. Due to recent advances, methods to characterize strains have become easier with mass spectrometry. Antimicrobial susceptibility testing is a must for definite treatment as C. ulcerans can be resistant to first-line antibiotic therapy. If resources are available, it is prudent to find if there is any toxin production. Here, we describe a rural farmer in central Missouri presenting with acute-onset right knee pain diagnosed with right prepatellar bursitis with abscess due to C. ulcerans infection. He recovered with surgical debridement and antimicrobial therapy. This is the first case of C. ulcerans causing prepatellar bursitis with an abscess as per medical literature review.